A New Signal of the Solar Magnetic Cycle: Opposite Shifts of Weak Magnetic Field Distributions in the Two Hemispheres - Tibebu Getachew; Ilpo Virtanen; Kalevi Mursula (Geophysical Research Letters)
Abstract We study the asymmetric distribution of weak photospheric magnetic field values in the two hemispheres separately using synoptic maps from Solar Dynamics Observatory/Helioseismic and Magnetic Imager, Synoptic Optical Long‐term Investigations of the Sun/Vector SpectroMagnetograph, and Wilcox Solar Observatory during Solar Cycles 21–24. We calculate the weak‐field asymmetry (shift) by fitting the distributions of weak‐field values to a shifted Gaussian. Hemispheric shifts derived from the three data sets agree very well and increase systematically when reducing the spatial resolution of the map. Shifts of the Northern and Southern Hemispheres are typically opposite to each other. Shifts follow the evolution of the trailing flux and have a strong solar cycle variation with maxima in the early to mid declining phase of the solar cycle. The sign of the hemispheric weak‐field shift is always the same as the polarity of the polar field in the respective hemisphere and solar cycle. We also find that shifts in the south are systematically larger in absolute value than in the north.